Use of Antibiotic-Impregnated DuraGen® to Reduce the Risk of Infection in Dura Repair: An In Vitro Study - Kaplan, M.; Akgun, B.; Demirdag, K.; Akpolat, N.; Kozan, S. K.; Cagasar, O.; Yakar, H. (Georg Thieme Verlag Kg, 2011)
Aim: To investigate the efficacy of antibiotic-impregnated DuraGen (R) in preventing infection when used for repair of dural defects. Material and Methods: 2 groups of 7 samples were formed. In the first group, normal DuraGen (R) samples without antibiotic impregnation and in the second group, DuraGen (R) samples with antibiotic impregnation (30mg vancomycin) were used. Staphylococcus aureus (ATCC 25923), and Staphylococcus epidermidis (ATCC 12228) were selected for this study. Antimicrobial efficacy was evaluated by counting the number of colonies on and by measuring the diameter of the inhibition zone around the samples. Results: There was no zone diameter around the normal DuraGen (R) for the 2 types of bacteria. There was significant bacterial growth (10(5)) according to the colony count. For antibiotic-impregnated DuraGen (R), there was a zone with a mean diameter of 32 mm in the agar with S. aureus and a zone with a mean diameter of 35 mm in the agar with S. epidermidis. Antibiotic-impregnated DuraGen (R) was quite effective against both microorganisms and there was no bacterial growth according to the bacterial colony count. Conclusions: In our in vitro study, antibiotic-impregnated DuraGen (R) material significantly inhibited microorganism growth. Our results show that antibiotic-impregnated DuraGen (R) has the potential to prevent infection.
Keywords: antibiotic-impregnated DuraGen (R); contaminated wounds; dural repair; infection